Пути модернизации компьютерных сетей общежитий ХНУРЭ - Ткачев, В. Н.; Макиенко, К. А. (ХНУРЕ, 2011)
The problem of upgrading university campus computer network is considered. The ways to move on new technological solutions are discussed and presented.
Keywords: компьютерная сеть; модернизация; общежития ХНУРЭ